“We work by the second !” Piecework remuneration and occupational health and safety from an ethnicity- and gender-sensitive perspective - Stephanie Premji; Katherine Lippel; Karen Messing (Perspectives Interdisciplinaires sur le Travail et la Santé)
Few qualitative studies have described the mechanisms by which piecework influences health. We present the results of 25 interviews conducted between 2004 and 2006 in a large garment factory in Montreal. We describe the workforce, made up in large part of women and immigrants, the requirements and constraints of production, workers’ strategies favouring production and those favouring health, and the management and impact of the health problems experienced by workers. In addition, we compare the experience of piecework to its representation by various stakeholders (employers, workers, decision-makers, doctors) as reported in 62 decisions regarding compensation claims for work-related health problems rendered by the Commission des lésions professionnelles (C.L.P.) between 2000 and 2007, decisions pertaining to the garment industry and mentioning piecework. We examine the causes and discuss the implications of our results.